Leaf and grain infection of rice by Helminthosporium oryzae and their effect on yield components - Prabhu, Anne Sitarama; Lopes, Altevir de Matos; Zimmermann, Francisco José P. (Pesquisa Agropecuaria Brasileira, 2014)
A field trial with six rice cultivars (’CICA-4’, ’Canela de Ferro’, ’Chatão’ ’Comecru Zebu’, ’IAC 1246’ and ’IAC 47’) was utilized to study the relationship between leaf and grain infection caused by Helminthosporium oryzae Breda de Haan and their individual as well as combined effect on the principal yield components under upland conditions. Linear models were selected for establishing relationships between brown spot and yield determining components. The results demonstrated that the leaf infection did not significantly contribute to the variation in panicle number, spikelets/panicle or percentage filled grains in all of the six cultivars utilized. The reduction in grain weight was principally related to grain infection except in cv. ’Canela de Ferro’. The disease effect on a determined yield component was variable in different cultivars. The cultivar ’Comecru Zebu’ exhibited a high degree of tolerance to grain infection.